Effect of bariatric surgery on weight loss, inflammation, iron metabolism, and lipid profile. (March 2014) - Santos, J.; Salgado, P.; Santos, C.; Mendes, P.; Saavedra, J.; Baldaque, P.; Monteiro, L.; Costa, E.
Background and Aims: Accumulating evidence indicates that a state of chronic inflammation has a crucial role in the pathogenesis of obesity-related metabolic dysfunction. This study aims to evaluate changes in inflammatory process, iron metabolism, erythropoiesis, and lipid profile associated with weight loss after gastric banding surgery. Material and Methods: A total of 46 patients were evaluated before and 3 months after gastric banding surgery. A survey was conducted to record demographic data, body mass index, and presence of comorbidities. Moreover, complete blood cell counts and serum levels of iron, ferritin, transferrin, high-sensitivity C-reactive protein, total cholesterol, low-density lipoprotein–cholesterol, high-density lipoprotein–cholesterol, and triglycerides were performed. Results: At a follow-up 3 months after surgery, our patients presented a significant decrease in weight and body mass index, associated with a decreased inflammatory process (decreased high-sensitivity C-reactive protein, neutrophil counts, and neutrophil:lymphocyte ratio), increased iron availability (increased transferrin saturation and a trend to higher iron serum levels), and significant decreased triglycerides and triglycerides:high-density lipoprotein–cholesterol ratio. Conclusions: Our results showed a significant decrease in the inflammation process 3 months after gastric banding surgery, associated with adipose tissue loss. This decrease in the inflammatory process is associated with more efficient iron absorption and increased iron availability for erythropoiesis. Moreover, we also found decreased triglyceride serum levels. These changes suggest benefits of weight loss, including decreased risk of cardiovascular disease.